Interventional Radiology in Renal Trauma - Gorsi, Ujjwal; Shivaji, Siva Chander (Digestive Disease Interventions, 2025)
Renal trauma is a significant concern in cases of abdominal injury, with its incidence varying from 1 to 10%, depending on the severity of the trauma. Most injuries stem from blunt trauma, such as vehicle accidents, and are observed predominantly in young males. Diagnostic imaging, particularly multiphasic CT, is crucial for accurate assessment and guiding treatment decisions. In cases where intervention is required, interventional radiology (IR) techniques play a pivotal role. This review outlines the various aspects of renal trauma management, focusing on the role of IR interventions. From diagnostic imaging modalities to endovascular techniques like angioembolization, the review offers insights into the comprehensive approach to renal trauma care. Understanding the anatomical considerations, imaging protocols, and treatment options in IR is essential for improving patient outcomes and reducing morbidity and mortality associated with renal trauma.
Keywords: interventional radiology; renal trauma; embolization